Acceptable attitudes and the limits of tolerance: Understanding public attitudes to conscientious objection in healthcare. (September 2019) - Haaland Barlaup, Astrid; Elise Landsverk, Åse; Kåre Myskja, Bjørn; Supphellen, Magne; Magelssen, Morten
Background: The public's attitudes to conscientious objection (CO) are likely to influence political decisions about CO and trust towards healthcare systems and providers. Few studies examine the public's attitudes in an in-depth way. Methods: Six hypotheses about public attitudes to CO were devised and a questionnaire designed in order to test them. A total of 1617 Norwegian citizens completed the online questionnaire. Results: Support for toleration of CO was strongest in the case of ritual circumcision of infant boys, lower for assisted dying and abortion. Attitudes to the procedure itself negatively predicted attitudes to CO for the procedure. Respondents were more accepting of CO to performing abortion than of CO to referrals for abortion. There was stronger support for CO as an outcome of local pragmatic arrangements than for CO as a statutory right. Conclusions: Instead of viewing CO as a 'moral safety valve' or minority right which is due also to those with whom we disagree strongly, a portion of the public approaches the issue from the angle of what moral attitudes they deem acceptable to hold. The gap between this approach on the one hand and human rights principles on the other is likely to give rise to tensions in political processes whenever policies for CO are negotiated.